Simulation and Experimental Verification of the Flooding and Draining Process of the Tidal Energy Converter “Deltastream” during Deployment and Recovery - Rocolle, Guillaume (Cranfield University, 2014)
Deltastream is an on-going project carried by Tidal Energy Limited since almost twenty years. It is a tidal energy converter with a triangular shape and one turbine on each tower. It has gone through many evolutions of design but a first prototype will be installed in the end of 2014 at Ramsey Sound. The deployment and recovery operations will be carried out with a single lift point through a heavy lift frame. Two issues have to be tackled during the operation: the rate of flooding of the ballasts and the tension on the lift crane cable. The most favourable sea state must be found in order to minimise the crane cable tension as well as the best inlets and outlets configuration for the ballasts system. In order to tackle those issues, preliminary analytical work was conducted on the demonstrator to assess the stability during the flooding process. A scaled model was designed and built in order to be tested in a wave-towing tank. The results from the tests highlight that the deployment and the recovery operations are safe for both the barge and Deltastream for the range of wave conditions tested in the tank. However, the sea state has an important impact on the proceeding of the operations, especially the period of the waves.
Keywords: Tidal turbine; stability; flooding process; snatch load; wave-towing tank